High-grade mucoepidermoid carcinoma in thyroglossal cyst: Post-surgical histological surprise and dilemmas - Chirukandath, Ravindran; Nimisha, CR; Babu, PJ; Arya, Puthukatt Muraleedharan; Lekshmi, RS; Santhosh, TV (Asian Journal of Medical Sciences, 2021)
Occurrence of malignancy in the TG cyst has been rarely reported, though rare, and papillary carcinoma predominates the common type but squamous cell carcinomas, anaplastic carcinoma, and medullary have been reported rarely. Mucoepidermoid carcinomas are most commonly seen in salivary glands, and as per the available literature, there was only two cases reported in thyroglossal cyst. We are presenting a 67-year-old lady presented with a 6×8 cm hard swelling below symphysis menti with no thyromegaly and moving on protrusion of tongue, and on MRI, it was found to be thyroglossal cyst with infiltration of strap muscles. Cytological investigation revealed it to be a TG cyst malignancy. The patient underwent total thyroidectomy and radical Sistrunk’s operation. Histopathological and immunohistochemistry revealed it to be a histological examination revealed a low-grade mucoepidermoid carcinoma consistent with origin in a thyroglossal duct remnant it invaded the hyoid bone and adjacent strap muscles. Various diagnostic and treatment dilemmas in the treatment of TG cyst malignancy are discussed with reference to mucoepidermoid carcinoma. We are reporting an usual histological surprise in a thyroglossal cyst malignancy being the only second reported case of TG cyst mucoepidermoid carcinoma this case highlights the importance of removal of thyroglossal duct cysts at an early stage and aggressive surgical approach in high-grade tumors.